2021
DOI: 10.1177/03616843211013465
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Compassion and Self-Esteem Writing Interventions on Women’s Valuation of Weight Management Goals, Body Appreciation, and Eating Behaviors

Abstract: In this study, we examined the effects of body-focused daily self-compassion and self-esteem expressive writing activities on women’s valuation of weight management goals, body appreciation, bulimic symptoms, and healthy and unhealthy eating behaviors. One-hundred twenty-six women, recruited from the community and a university participant pool ( Mage = 29.3, SD = 13.6), were randomly allocated to one of the three writing conditions: body-focused self-compassion, body-focused self-esteem, or control. Women refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 80 publications
(172 reference statements)
2
8
0
1
Order By: Relevance
“…Results highlight the benefits of self-compassion for adaptive eating behaviors and may suggest that increasing self-compassion in adult women could support their ability to engage in intuitive eating. There exist many methods of increasing self-compassion in women that are both effective and cost-efficient, such as writing activities, that aid emotion regulation and lower disordered eating [46,51]. It is plausible that increasing women's self-compassion through an intervention could help them cope with negative interpersonal experiences elicited by perceived abandonment (i.e., attachment anxiety) or lack of support (i.e., attachment avoidance), and in turn, help nurture their intuitive eating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results highlight the benefits of self-compassion for adaptive eating behaviors and may suggest that increasing self-compassion in adult women could support their ability to engage in intuitive eating. There exist many methods of increasing self-compassion in women that are both effective and cost-efficient, such as writing activities, that aid emotion regulation and lower disordered eating [46,51]. It is plausible that increasing women's self-compassion through an intervention could help them cope with negative interpersonal experiences elicited by perceived abandonment (i.e., attachment anxiety) or lack of support (i.e., attachment avoidance), and in turn, help nurture their intuitive eating.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than mixing negative perceptions with themselves, individuals acknowledge that their thoughts and emotions are just that, which helps dispel their irrational beliefs [50]. Previous studies employing self-compassion interventions have demonstrated that increased selfcompassionate coping is conducive to better emotion regulation as indicated by lower levels of negative affect [46] and reduced emotionally-driven eating as indicated by lower bulimic symptoms [51]. These findings may suggest that women's degree of self-compassion may play a role in how they perceive and respond to negative interpersonal environments, and in turn, relate to how they approach eating.…”
Section: Self-compassionmentioning
confidence: 99%
“…Similar results have been obtained in research comparing the efficacy of self-compassion and self-esteem interventions within the context of eating disorders and body dissatisfaction: Self-compassion-inducing writing produced more positive bodily feelings and greater reduction in eating disorder symptoms than self-esteem-inducing writing. [75][76][77] In conclusion, while these were all studies with non-clinical samples in which a rather simple manipulation of selfcompassion and self-esteem was conducted by means of writing exercises, the results nevertheless indicated that induced self-compassion is associated with better outcomes than induced self-esteem. Together with the observation that selfcompassion appears easier to generate, one might conclude that interventions targeting this characteristic have greater potential for building resilience and well-being than interventions focusing on self-esteem.…”
Section: Compassion-focused Interventionsmentioning
confidence: 81%
“…Similar results have been obtained in research comparing the efficacy of self-compassion and self-esteem interventions within the context of eating disorders and body dissatisfaction: Self-compassion–inducing writing produced more positive bodily feelings and greater reduction in eating disorder symptoms than self-esteem–inducing writing. 75–77 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, negative thoughts towards body image and body shape occur as a unique and conclusive factor in the origin of this BD and the symptomatology that may be associated with it [ 14 , 35 ]. It is known that externalizing thoughts about the body appears to help decrease BD and ED symptomatology [ 36 ], so studying the thoughts of people with obesity during treatment using a qualitative methodology could be key to understanding, from a more global perspective, the progress made during the sessions. However, there are few studies that use this type of methodology, and even fewer longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%